In vitro and in vivo assessment of the benzydamine-mediated interference with the hepatic S-oxidation of the anthelmintic albendazole in sheep - Virkel, Guillermo Leon (2014)
The aim of this research was to investigate the influence of benzydamine (BZ) on the in vitro and in vivo hepatic metabolism of the anthelmintic albendazole (ABZ) in sheep. The enantioselective ABZ S-oxidation was assessed by the amount of its (−) and (+) ABZ-sulphoxide (ABZSO) enantiomers formed in sheep liver microsomes (in vitro work). In the in vivo trial, lambs received ABZ (5 mg/kg, intra-ruminal route) or ABZ (5 mg/kg) plus BZ (8 mg/kg, i.m., two doses 4 h apart). Incubated and plasma samples were analysed by HPLC. In vitro, BZ IC50s (the concentrations that produced a 50% decrease in ABZ S-oxidation) for the production of total ABZSO and (+)ABZSO were 71.0 ± 8.1 and 62.6 ± 8.1 μM, respectively. BZ showed a strong inhibitory potency over the flavin-monooxygenase (FMO)-dependent production of (+)ABZSO compared to the cytochrome P450 (CYP)-mediated production of (−)ABZSO. In vivo, co-administration of BZ with ABZ did not change the pharmacokinetic parameters of ABZSO and ABZSO2 with the exception of significantly higher (p < 0.01) formation half-lives (t1/2for) for (−)ABZSO (3.24 ± 1.03 h vs. 6.19 ± 2.18 h) and (+)ABZSO (3.87 ± 1.20 h vs. 7.21 ± 2.46 h). BZ inhibited the hepatic FMO and CYP-dependent S-oxidation of ABZ in vitro. However, the metabolic interaction between ABZ and BZ was not observed in the in vivo pharmacokinetic trial. Hence, further work using a different dosing scheme or pharmaco-technical preparation of BZ may be required to observe in vivo the metabolic interference clearly shown under in vitro conditions.